Temporal Characteristics of English Spoken by Native Speakers of Croatian - Horga, Damir; Mildner, Vesna (1999)
A group of 20 Croatian native speakers with various levels of English proficiency and a group of 7 English native speakers read a short passage of English prose, which was recorded and digitized, and the PCquirer computer program was used to obtain waveforms and spectrograms to measure selected variables. 10 English language experts assessed the level of subjects' English pronunciation proficiency. Croatian speakers were compared with the group of English native speakers by means of discriminative analysis in the following sets of variables: segmental duration (35 selected sounds), sentence and clause pauses durations, feet duration and several rate-of-speech variables. Regression analysis was used to show which of the temporal characteristics participated in predicting the pronunciation proficiency. It was shown that not all of the temporal characteristics of Croatian spakers speaking English that are significantly diffeent from native English speakers had the corresponding influence on foreign accent assessment.
Projekt MZOS
ENG